Exploring the career maze: An investigation of career intentions of medical graduates in Pakistan: A qualitative study: Career intentions of medical graduates in Pakistan - Siddiqui, Zarrin SEEMA (Pakistan Journal of Medical Sciences, 2019)
Background & Objectives: Pakistan faces a number of challenges in medical education. While there is an increase in the number of medical schools across the country, there is a dearth of practicing doctors in rural areas as well as a shortage of specialists in various fields specially in surgical specialties. Similarly, the number of doctors migrating overseas is also increasing due to security concerns. This requires investigation of the factors that influence career intentions of medical graduates in Pakistan. As there is no validated instrument available within Pakistani context, this qualitative study was designed to examine medical graduates’ reasons for their career intentions in light of Ajzen’s Theory of Planned Behavior (TPB). Methods: Five focus group discussions were conducted in two cities of Pakistan i.e. Karachi and Hyderabad during November – December 2012. These were then transcribed and were coded into the three primary attributes of TPB i.e. behavioral, normative and control beliefs by comparing similarities and differences. Results: The results suggest that there is a variation in the factors that influence the career intentions of the medical students. In addition a number of new themes were identified which have not been reported earlier in studies elsewhere and are specific to this region. This needs further examination by stakeholders for intervention. Conclusion: The analysis of data from the focus groups confirms the theoretical framework and identifies a range of influencing factors, at different stages of education and practice. As the study was limited to a smaller number of graduates and all except one graduate wanted to continue practice, a larger sample may be required for the purpose of generalization of the findings reported in this study. doi: https://doi.org/10.12669/pjms.35.5.465 How to cite this: Siddiqui ZS. Exploring the career maze: An investigation of career intentions of medical graduates in Pakistan: A qualitative study. Pak J Med Sci. 2019;35(5):1456-1460. doi: https://doi.org/10.12669/pjms.35.5.465 This is an Open Access article distributed under the terms of the Creative Commons Attribution License (http://creativecommons.org/licenses/by/3.0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.